2009
DOI: 10.1057/rlp.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Strategic and operational factors' influence on the management of building maintenance operation processes in sports and leisure facilities, Hong Kong

Abstract: Hackman Hon Yin Leeis Chartered Surveyor (UK), Registered Professional Surveyor (HK), Certifi ed Facility Manager (USA) and Registered International Engineering Technologist (HK) with over 20 years of experience in the fi eld of operation and maintenance of building services engineering systems, building maintenance and facilities management. Recently, he obtained a doctoral degree from the University of South Australia and his completed research work examines the gaps between top management and maintenance pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The main topics covered in the bibliographic review are briefly described as follow: An analysis of the general fundamentals of BMM. Works with analogous points or features identified – Yin Lee and Scott (2009), Straub (2012), Falorca et al (2013a), Lateef Olanrewaju and Abdul-Aziz (2015) and Mydin (2017). A bibliometric study, with the aim of creating the basis of a catalogue of bibliographic resources, to be used in conjunction with the SIAPME future computerised platform and to be made available to SIAPME users and managers. Studies can be found, some reflecting upon bibliometric analysis (Falorca et al , 2014; Santos et al , 2017), literature searches (Wing et al , 2016) and literature analysis and reviews (Au-Yong et al , 2016; Che-Ghani et al , 2016; Puķīte and Geipele, 2017; Lohmann et al , 2017; Galán and Gómez, 2018; Chong et al , 2018).…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The main topics covered in the bibliographic review are briefly described as follow: An analysis of the general fundamentals of BMM. Works with analogous points or features identified – Yin Lee and Scott (2009), Straub (2012), Falorca et al (2013a), Lateef Olanrewaju and Abdul-Aziz (2015) and Mydin (2017). A bibliometric study, with the aim of creating the basis of a catalogue of bibliographic resources, to be used in conjunction with the SIAPME future computerised platform and to be made available to SIAPME users and managers. Studies can be found, some reflecting upon bibliometric analysis (Falorca et al , 2014; Santos et al , 2017), literature searches (Wing et al , 2016) and literature analysis and reviews (Au-Yong et al , 2016; Che-Ghani et al , 2016; Puķīte and Geipele, 2017; Lohmann et al , 2017; Galán and Gómez, 2018; Chong et al , 2018).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Although BM activity may have, in the short or medium term, a significant strengthening of its scale of implementation, it seems that it is already facing with even demanding customers and situations, seeking effective services of higher quality and speed, without involving significant increases in costs. The challenges of effectiveness of maintenance strategies have already been analysed by Yin Lee and Scott (2009) and some of the other biggest BM challenges are also indicated by Christiansen (2018).…”
Section: Introductionmentioning
confidence: 98%
“…Sports facilities are categorized as hospitality facilities and the facilities require high level of services and attention because their expectation is usually high (Lee & Scott, 2009). According to Chan et al (2001), hospitality facilities are more complicated in construction and installation, thus it leads to higher maintenance cost.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance requirements here are comparatively more demanding. Therefore it is important to have a well-developed maintenance practice to support the maintenance of these facilities (Lee & Scott, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation